Eurasian Economic Union - a New Call to the West - Leonid Grigoryevich Ivashov (Управленческое консультирование, 2018)
The article is devoted to the main aspects of development of the Eurasian Economic Union. Authors concretize that now Eurasian Economic Union is an economic union but it has every chance to become the political union. The attention to obstacles for development of Eurasian Economic Union and to calls which the Eurasian Economic Union puts before the West is paid.